Association Rule Algorithms for Logical Equality Relationships - Chyuan-Meei Chen; Shu-Hsien Liao (Proceedings : 8th IEEE International Conference on Computer and Information Technology Workshops ; CIT Workshops 2008 : 8-11 July 2008, Sydney, Australia, 2008)
The association rule has become one of the most important techniques in data mining. New algorithms must be developed in order to apply it to more areas. This paper proposes association rule algorithms for logical equality relationships, modified from the original Apriori and FP-Growth algorithms. Logical equality is defined as truerarrtrue (1rarr1) or falserarrfalse (0rarr0) associations. This special relationship commonly occurs in the real world, such as the linkage in the stock markets and customer loyalty for a certain product.